Running mechanics and metabolic responses with water bottles and bottle belt holders - Vincent, H. K.; Zdziarski, L. A.; Fallgatter, K.; Negron, G.; Chen, C.; Leavitt, T.; Horodyski, M. B.; Wasser, J. G.; Vincent, K. R. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To determine whether differential kinematics, kinetics, rates of energy use, and cardiopulmonary responses occur during running with water bottles and bottle belt holders compared with running only. Methods: Trained runners (N=42; age 27.2 [6.4] y) ran on an instrumented treadmill for 4 conditions in a randomized order: control run (CON), handheld full water bottle (FULL; 16.9 fluid oz; 454 g), handheld half-full water bottle (HALF; 8.4 fluid oz; 227 g), and waist-worn bottle belt holder (BELT; hydration belt; 676 g). Gas exchange was measured using a portable gas analyzer. Kinetic and kinematic responses were determined by standard 3-dimensional videographic techniques. Interactions of limb side (right and left) by study condition (CON, FULL, HALF, and BELT) were tested for rates of oxygen use and energy expenditure and kinematic and kinetic parameters. Results: No significant limb-side×condition interactions existed for rates of oxygen use or energy expenditure. A significant interaction occurred with sagittal elbow flexion (P<.001). Transverse pelvic-rotation excursions differed on average 3.8° across conditions. The minimum sagittal hip-flexion moment was higher in the right leg in the HALF and BELT conditions compared with CON (P<.001). Conclusions: Carrying water by hand or on the waist does not significantly change the kinematics of running motion, rates of oxygen use and energy expenditure, or cardiopulmonary measures over short durations. Runners likely make adjustments to joint moments and powers that preserve balance and protect the lower-extremity joints while maintaining rates of oxygen use and energy expenditure.